35 Principles of care for the dying patient- audit of use in a tertiary referral cancer centre. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Halley, A; Ramsay, J; Johns, H; Kane, G; Stephens, A; Stevens, AM
Abstract : Background: The Leadership Alliance for the Care of Dying People set out an approach with focus on achieving the five priorities of care. Our trust developed an electronic version of the London Cancer Alliance document, The Principles of Care for Dying Patients. This audit set out to determine the number of expected deaths who had a document in place and if completed, adherence to the NICE Quality Standards for care of adults in the last days of life (NG31). Methods: Prior to the National Care at the end of life Audit, the hospital palliative care team undertook an audit of care of patients in the last days of life for deaths from 1st April 2017 to 31st March 2018. There were 230 deaths across the trust. Deaths in critical care and paediatric deaths were excluded. 177 case record reviews were undertaken by the palliative care team. Results: 65% of patients who were recognised as dying had a principles of care document initiated. NICE Quality Standard 1: 100% of patients had daily review to assess for changes in dying phase, i.e. nearing death, stabilising or recovering. NICE Quality Standard 2: 53% of patients had capacity to be able to discuss, and review an individualised care plan (ICP). 97% of cases showed documented evidence of a family discussion to ensure communication of recognition of dying and development of ICP. NICE Quality Standard 3: – 94% of patients had appropriate anticipatory medications prescribed. NICE Quality Standard 4%–68% of patients had documented evidence of discussion of hydration status. Conclusion: The Principles of Care Document when used adheres to the Nice Quality Standard. The regular education of the multi-disciplinary team in caring for dying patients continues to focus on use of the document to direct excellent care of the dying.